Properties of glue-laminated timber manufactured from viscoelastic-thermal compression modified paraserianthes falcataria laminas - Charles Michael Albert (2022)
Shortage in timber supply is a major concern for wood-based industry since the last two decades, where the existing medium-heavy hardwood have long rotation age. Paraserianthes falcataria is a fast-growing tree species that have short-rotation age, but possessed poor physical and mechanical characteristics, which limits its range of application. However, these properties can be improved by densification. Previous studies reported that densification technology had enhanced the density and mechanical strength of wood. Therefore, in this study, laminas from Paraserianthes falcataria underwent viscoelastic-thermal compression (VTC). This study evaluated (1) the physical and anatomy properties of the VTC modified laminas, (2) the physical and mechanical properties of glulam manufactured from VTC modified laminas, and (3) the relationship between properties of the VTC modified laminas and glulam. During VTC treatment, the laminas were pre-steamed, compressed with heat, and underwent cooling phase. Five different parameters, including control, were applied, denoted as S1/D (10 minutes pre-steamed, densified), S2/D (20 minutes pre-steamed, densified), S3/D (30 minutes pre-steamed, densified), NS/D (non-pre-steamed, densified), and control (NS/ND: non-pre-steamed, non-densified). VTC modified laminas were also processed to make glulam panels. The outcome from lamina tests showed that S1/D had the highest density (density: 623.30 kg/m3, density profile: 590.22 kg/m3) whilst having the lowest moisture content (7.64%) and springback rate (0.71%). Besides that, S1/D also achieved the lowest contact angle (water: 11.78˚, polyvinyl acetate: 74.72˚), which indicated good wettability for bonding purpose. In contrast, morphological analysis revealed that S3/D had the highest rate of cell lumen deformation (39.61 μm2), which is supposed to be indicative of higher density and contact angle. As for the physical properties of glulam, S2/D acquired the highest water absorption and thickness swelling with values of 106.49% and 50.87%, respectively. On the other hand, S3/D had the lowest values in those tests, and obtained the highest delamination rate (73.97%). In relation to morphological analysis, a higher rate of cell lumen deformation reduced the water absorption and decrease the bonding efficiency. Despite of having poor physical properties, the glulam of S3/D obtained the highest resistance against elastic deformation and rupture, as indicated by the findings from static bending and compression tests. S1/D, on the other hand, have the highest shearing strength (2.89 N/mm2) and hardness (radial: 1986.00 N, longitudinal: 2953.20 N). The correlation analysis showed that the MOE (edgewise) and density profile of lamina of S3/D have a significant, highly strong positive relationship. In summary, VTC treatment enhanced the physical properties of Paraserianthes falcataria laminas by 49.16%, while physical and mechanical properties of glulam were also improved by 45.71% and 50.08%. The treatment also reduced the cell lumen area by 49.51%. 10 minutes of pre-steaming was the ideal duration to increase the physical properties of laminas and glulam, while 30 minutes of pre-steaming have remarkably enhanced the mechanical properties. The correlation analysis indicated that increase in density of lamina enhanced the mechanical strength of glulam, where 30 minutes of pre-steaming showed a significant positive relationship.